What could Colorado Springs be like in the future?/ Vision Statement (The gazette (Colorado Springs, Colo.), 1996)
Colorado Springs is truly the "America the Beautiful" city. We preserve our natural environment in balance with economic diversity and vitality. Our quality of life reflects the good health, enriched culture and human inspiration offered to all. We are a safe and caring community where government, citizens, businesses and other organizations actively cooperate to accomplish community goals.